Relationship Of Self-Concept, Social Support And Depression On The Quality Of Life In Diabetes Mellitus - Indriyati Indriyati; Eny Purwandari (NurseLine Journal, 2021)
Background: Diabetes mellitus is a disease that cannot be cured but can be managed both physically and psychologically. The majority of DM patients are very pessimistic about the recovery of their illness. Purpose: This study aims to find out 1) the role of depression as a mediator variable between self-concept variables and social support for the quality of life of DM patients, 2) the role of self-concept of depression, 3) the role of social support against depression and 4) the role of depression in quality of life. Methods: This study was 253 patients with diabetes mellitus at hospital dr. Moewardi Surakarta. Sampling in this study was purposive sampling. Data collection used the Beck Depression Inventory (BDI) questionnaire, Tennese Self Concept Scale (TSCS), the Hersarling Diabetes Family Support Scale (HDFSS) and the Word Health Organization Quality of Life (WHOQOL). Data analysis used path analysis method (path analysis) and strengthened by sobel test test. Results: The study showed that there was a correlation between self-concept, social support and depression on the quality of life of patients with diabetes mellitus which was characterized by the p-value of self-concept of 0.002, p value of social support, depression and quality of life of 0,000. The results of path analysis show that depression is able to be a mediator between self-concept and quality of life and the mediterator between social support for quality of life. this result is reinforced by the sobel test showing a value of> 1.98 with a significance level of 5%. Conclusion: Depression can be a mediator between self-concept and quality of life and depression is also able to be a mediator between social support and quality of life.